Comparative evaluation of artificial saliva and complete artificial saliva as solvent vehicles for in vitro toxicity testing of oral tobacco products - Cao, Xuefei; Farcas, Mariana T.; Prepelitskaya, Yevgeniya V.; Ritzenthaler, Abaigeal; Molignano, Jennifer; Oldach, Jonathan; Gutierrez, Marisol M. (Frontiers in Toxicology, 2025)
BackgroundOral tobacco-derived nicotine (OTDN) pouches are tobacco-free products and are considered potential reduced-risk alternatives to traditional tobacco products within the tobacco harm reduction framework. Despite their growing popularity, the local oral toxicity profiles of OTDNs remain poorly characterized. Although in vitro toxicity studies have been conducted, the lack of standardized testing protocols, including solvent vehicle selection, limits data comparability across laboratories. To address this, we evaluated and compared the biological effects of artificial saliva (AS) and complete artificial saliva (CAS) across four in vitro oral models to identify an appropriate solvent vehicle for mechanistic testing.MethodsExtraction efficiency was first assessed using the Swedish-style reference snus pouch CRP1.1 extracted in AS and CAS from 10% to 30% w/v concentrations. Nicotine and tobacco-specific nitrosamines (TSNAs) were quantified for extraction efficiency. The biological effects of AS and CAS, including cytotoxicity, oxidative stress, and inflammatory responses, were evaluated across four in vitro oral models, including monolayer normal human gingival fibroblasts (NHGFs) and oral epithelial cells (NHOEs), as well as 3D organotypic models (EpiOral™ and EpiOral™ Full Thickness).ResultsThe results showed comparable nicotine extraction efficiency between AS and CAS, with no significant impact from pouch cutting size or extraction duration. However, AS demonstrated higher efficiency in extracting TSNAs compared to CAS at 10% and 20% w/v, with the extraction efficiency decreasing as extract concentrations increased.Neither AS nor CAS induced cytotoxicity in any of the oral models. CAS triggered oxidative stress at the highest concentration in ORL-300-FT. Both AS and CAS elicited concentration-dependent pro-inflammatory responses in NHGFs and NHOEs. Specifically, AS increased both IL-6 and IL-8 secretion in NHOEs, while CAS elevated IL-8 release in both NHGFs and NHOEs but exhibited opposing effects on IL-6 secretion in NHOEs. In the organotypic tissue models, both AS and CAS reduced IL-6 secretion without significantly affecting IL-8 levels.ConclusionThese findings emphasize the importance of evaluating additional biological responses alongside cytotoxicity in vehicle control studies. CAS and ORL-300-FT were chosen for future testing due to their minimal vehicle effects and greater biological relevance, providing a robust platform for assessing oral tobacco product toxicity.